Escuta, gravação, plataforma web : fazer mapa sonoro como conjunto de práticas de mídia - Aragão, Thaís Amorim (Universidade do Vale do Rio dos Sinos, 2018)
This work investigates soundmapping within Sybille Krämer's theoretical framework on what a medium is. According to the philosopher, in a transmission, medium is what seems to disappear behind the sensible surface of what comes to appearance. Based on her ideias, we developed a theoretical tool called mediological dial, in order to auscultate media processes involved in the constitutive practices of this new cartography. Our aim was to identify what becomes transparent and which opacity corresponds to it, in the course of a chain of transmissions. We assumed Krämer's proposal of a media-critical epistemology, understanding that the messenger and the trace, the representation and the conditions of its production are two inseparable dimensions of media, as well as two complementary and interdependent epistemological positions. Field research was also guided by Rob Kitchin and Martin Dodge's post-representational approach to cartography. They suggest tracking how a particular process of map-making emerges. We reconstituted the development of the Radio Aporee platform's sound map, since its origins in the net art of the 1990s, and found a situation in which sound is a fundamental element in a strategy to reveal media spaces. In the context of this research, sound map is considered as a hybrid audiovisuality made possible by the digitalization and which operates between two strong traditions: the map and the sound recording.
Keywords: Filosofia da mídia; Espaço; Som; Materialidades; Cartografia; Media philosophy; Space; Sound; Materialities; Cartography; ACCNPQ::Ciências Sociais Aplicadas::Comunicação